Human Language Technologies As a Challenge for Computer Science and Linguistics – 2023 - Zygmunt Vetulani; Patrick Paroubek (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2023)
The monograph is a part of activity of fostering sound development of language technologies aiming at facing new challenges in the world marked by the COVID-19 pandemic, wars in Europe, mass migrations and natural disasters at the scale not seen since many years. In the volume are presented contributions by 186 authors from more than 20 countries from Africa, Asia, Australia, Europe and North America. The contributions to this book cover large area of language technologies and related fields.